Spatiotemporal variation in community structure of marine benthic ciliates in the Yellow Sea during and after macroalgal and giant jellyfish blooms - 周百灵 徐奎栋 (Chinese journal of oceanology and limnology, 2016)
The annual bloom of the green macroalgal Ulva prolifera from May through July since 2008 and another of giant jellyfi sh Nemopilema nomurai from June through September have been frequent events in the Yellow Sea. However, the patterns of benthic ciliate communities during and after the blooms are still not known. In combination with analyses of benthic environmental factors, we investigated the distribution and community composition of benthic ciliates in the Yellow Sea in July and November 2011. In July, ciliates had high standing crops and diversity in the northern Yellow Sea, and in the inshore area off the southern Shandong Peninsula, where large numbers of green macroalgae accumulated. In November, the abundance, biomass and diversity of ciliates were high in the sea areas off the Shandong Peninsula and Changjiang estuary, where a large quantity of jellyfi sh occurred in August. Neither the abundance nor the biomass had signifi cant diff erence between seasons, or between diff erent compartments of the Yellow Sea. The species number, and both Margalef and Shannon-Wiener indices of ciliates were all signifi cantly higher in November than in July. In both seasons, prostomateans and karyorelicteans consistently constituted the fi rst and second most important ciliate groups in biomass; and carnivorous ciliates constituted the primary feeding type in terms of biomass as well as species richness, followed by bacterivores, algivores and omnivores. Compared with that in June 2007 when no macroalgae occurred, the percentage of small-sized bacterivores（e.g. Metacystis spp., Euplotes spp. and scuticociliates） increased in July 2011. The proportion of carnivorous ciliates increased in November, and this increased dominance of carnivorous ciliates may be a response to the increase in predominance of heterotrophic nanofl agellates, which might in turn be ascribed to an eff ect of green macroalgal and giant jellyfi sh blooms in the Yellow Sea.